Environmental DNA monitoring of waterfowl reveals community changes during migration - Luciana Guimaraes de Andrade; Steve Michael Bogdanowicz; Holger Klinck; David Lodge; Jose A. Andrés (PLoS ONE, 2026)
Large-scale monitoring of wildlife populations is a cornerstone of effective conservation and resource management, particularly for highly mobile taxa whose distributions shift rapidly across space and time. In this paper we explore the possibility of using environmental DNA-based surveys as a cost-efficient, complementary tool to estimate populations of North American waterfowl species. To achieve this, we first evaluated the performance of all currently available avian metabarcoding primers and compared them to newly designed primers targeting the mitochondrial ND2 gene within the Anatidae tribes of North America. All the existing avian assays showed strong cross-priming amplification with other vertebrates. In contrast, in-silico analyses of our waterfowl targeted assays showed a high degree (>90%) of avian specificity, encompassing all the 132 Anatidae species sequenced thus far. We used this targeted metabarcoding approach to track the temporal variation in the relative abundance of waterfowl species during the fall migration at Montezuma National Wildlife Refuge, New York, a major resting area for waterfowl on their journey to and from North American nesting areas. We compared eDNA results with visual surveys conducted by us and from those reported on eBird, a community science database. Our results showed that eDNA detected all waterfowl species (n = 25) observed during the visual surveys. Positive correlations existed between standardized amplicon sequence variant (ASV) counts and the relative abundance of waterfowl species as reported in eBird on the day of sampling and up to five days prior. Importantly, eDNA metabarcoding captured temporal shifts in community composition and species turnover during fall migration, highlighting its utility for tracking relative changes in waterfowl assemblages through time. As is often reported in metabarcoding studies, eDNA did not provide a good metric for absolute abundance of species; accordingly, only 8 out of 25 waterfowl species showed significant correlations between the number of eDNA reads and the total abundance of birds. Overall, while eDNA-targeted metabarcoding has not yet been applied to study bird communities extensively, our results demonstrate that this technique can be used as an effective complementary tool for assessing species composition of waterfowl communities and estimating relative abundance of species within those communities.